Composite membrane, battery and electric equipment

By adopting a composite membrane structure in the lithium battery, including a lithium supplement layer, a first base film and a second base film, the problem of severe heat generation and poor stability when supplementing lithium with the negative electrode is solved, and a higher Coulomb efficiency, energy density and longer cycle life are achieved.

CN119852646AActive Publication Date: 2025-04-18CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311863209.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-04-18
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

In the prior art, there are problems of severe heat generation and poor stability when supplementing lithium with negative electrodes.

Method used

A composite film is used, including a lithium supplement layer, a first base film and a second base film. The first base film carries a lithium supplement layer, and the second base film isolates the positive electrode sheet and the negative electrode sheet, so that the safety of the lithium supplement process of the battery is improved through this structure.

Benefits of technology

The battery's Coulomb efficiency, energy density and cycle life are improved, the heating problem of lithium metal is avoided when rolling with the negative electrode sheet is directly pressed, and prelithiation is completed under a closed vacuum, solving the consumption and storage safety of active lithium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852646A_ABST
    Figure CN119852646A_ABST
Patent Text Reader

Abstract

The invention provides a composite membrane and a battery, and the battery comprises the composite membrane which comprises a lithium supplementing layer; the first base film is arranged on one side of the lithium supplementing layer, and the first base film is configured to be suitable for bearing the lithium supplementing layer; the second base film is arranged on one side, far away from the lithium supplementing layer, of the first base film, and the second base film is configured to isolate the positive plate from the negative plate. The composite membrane comprises the two base membranes and the lithium supplementing layer, the first base membrane is used for bearing the lithium supplementing layer, the lithium supplementing layer can be arranged on the composite membrane in advance, and then the composite membrane is compounded with a positive plate and a negative plate, so that the safety of the lithium supplementing process of the battery is improved; and the problems of serious heating and poor stability when the lithium metal is directly rolled with the negative plate are avoided, so that the battery prepared from the composite film disclosed by the embodiment can have higher coulombic efficiency, higher energy density and longer cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and more specifically, to a composite film, a battery and an electrical device. Background Art

[0002] In the related art, when preparing lithium batteries, lithium can be supplemented at the negative electrode to form a pre-lithiated negative electrode to improve the initial efficiency and energy density of the negative electrode and improve the battery charge and discharge cycle. In the prior art, lithium supplementation of the negative electrode is usually carried out by pressing lithium powder or lithium foil with the negative electrode. However, the negative electrode material has the problem of severe heat generation and poor stability during contact with lithium metal. Summary of the invention

[0003] One purpose of the present application is to provide a new technical solution for a composite membrane, which can at least solve the problems of severe heat generation and poor stability during lithium replenishment of the negative electrode in the prior art.

[0004] Another object of the present application is to provide a battery comprising the above-mentioned composite membrane.

[0005] Another object of the present application is to provide an electrical device comprising the above-mentioned battery.

[0006] According to a first aspect of the present application, a composite membrane is provided, comprising: a lithium replenishing layer; a first base membrane, the first base membrane being arranged on one side of the lithium replenishing layer, the first base membrane being configured to be suitable for carrying the lithium replenishing layer; a second base membrane, the second base membrane being arranged on a side of the first base membrane away from the lithium replenishing layer, the second base membrane being configured to isolate the positive electrode sheet and the negative electrode sheet.

[0007] Optionally, the air permeability of the first base film is greater than the air permeability of the second base film.

[0008] Optionally, the air permeability of the first base film is ≤250s / 100ml.

[0009] Optionally, the air permeability of the second base film is 100s / 100ml to 500s / 100ml.

[0010] Optionally, the ionic conductivity of the first base membrane is greater than the ionic conductivity of the second base membrane.

[0011] Optionally, the ionic conductivity of the first base film is ≥6*10 -4 s / cm.

[0012] Optionally, the ionic conductivity of the second base film is 1*10 -4 s / cm~1*10 -2 s / cm.

[0013] Optionally, the material of the first base film includes at least one of polypropylene, polyethylene, polyester film, polyimide, polyetherimide, polyvinyl alcohol, polyacrylic acid, polyvinylidene fluoride, and polytetrafluoroethylene.

[0014] Optionally, the lithium supplement layer satisfies at least one of the following conditions: the thickness of the lithium supplement layer is 1 μm to 15 μm; the surface density of the lithium supplement layer is 1 g / m 2 ~8g / m 2 .

[0015] Optionally, an ablation layer is provided on a side of the first base film away from the lithium replenishing layer, and the ablation layer is configured to be able to chemically react with lithium.

[0016] Optionally, the ablation layer satisfies at least one of the following conditions: the ablation layer is configured to be capable of undergoing an intercalation reaction with lithium at 0.5V to 4V; the electronic conductivity of the ablation layer is less than 10 -7 s / cm; the thickness of the ablation layer is 0.5μm to 10μm; the surface density of the ablation layer is 1g / m 2 ~12g / m 2 .

[0017] Optionally, the material of the ablation layer includes at least one of titanium oxyfluoride, lithium titanate, lithium aluminum titanium phosphate, lithium lanthanum titanate, titanium dioxide, tungsten oxide, zinc oxide, and silicon oxide.

[0018] Optionally, a solid electrolyte layer is provided between the first base film and the lithium replenishing layer.

[0019] Optionally, the material of the solid electrolyte layer includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum zirconium oxide, lithium phosphate and doped products thereof.

[0020] According to a second aspect of the present application, a battery is provided, comprising a positive electrode sheet, a negative electrode sheet and a composite membrane, wherein the composite membrane is any composite membrane of the above embodiments.

[0021] According to a third aspect of the present application, there is provided an electrical device comprising a battery according to any one of the above embodiments.

[0022] According to the composite membrane of the present application, it includes two layers of base membrane and one layer of lithium replenishing layer. The first base membrane is used to carry the lithium replenishing layer, and the lithium replenishing layer can be pre-set on the composite membrane. The second base membrane is used to play the role of conventionally isolating the positive electrode sheet and the negative electrode sheet. The composite membrane is then compounded with the positive electrode sheet and the negative electrode sheet, which is beneficial to improve the safety of the battery lithium replenishing process and avoid the problem of severe heat generation and poor stability when lithium metal is directly rolled with the negative electrode sheet. Therefore, the battery made of the composite membrane of this embodiment can have higher coulomb efficiency, higher energy density and longer cycle life. In addition, the composite membrane of this embodiment does not need to be rolled when it is compounded with the positive electrode sheet and the negative electrode sheet to achieve pre-lithiation, so the pre-lithiation can be completed under a closed vacuum, solving the problem of active lithium consumption in the process of lithium replenishing the negative electrode sheet and the safety problem during storage.

[0023] Other features and advantages of the present application will become apparent from the following detailed description of exemplary embodiments of the present application with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the application and, together with the description, serve to explain the principles of the application.

[0025] Figure 1 is a schematic structural diagram of a battery according to a first embodiment of the present application;

[0026] Figure 2 is a schematic structural diagram of a battery according to a second embodiment of the present application;

[0027] Figure 3 is a schematic structural diagram of a battery according to a third embodiment of the present application;

[0028] Figure 4 is a schematic structural diagram of a battery according to a fourth embodiment of the present application;

[0029] Figure 5 is a schematic structural diagram of a first diaphragm in a composite membrane according to a fourth embodiment of the present application;

[0030] Figure 6 is a schematic structural diagram of a second diaphragm in a composite membrane according to a fourth embodiment of the present application;

[0031] Figure 7 This is a process flow chart of preparing the first diaphragm according to the fourth embodiment of the present application.

[0032] Reference numerals

[0033] Composite film 100; lithium supplement layer 11; solid electrolyte layer 12; first base film 13; ablation layer 21; second base film 22;

[0034] Positive electrode sheet 200;

[0035] Negative electrode sheet 300. DETAILED DESCRIPTION

[0036] Various exemplary embodiments of the present application will now be described in detail with reference to the accompanying drawings. It should be noted that unless otherwise specifically stated, the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present application.

[0037] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the present application, its application, or uses.

[0038] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered part of the specification.

[0039] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0040] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.

[0041] The composite film 100 according to the embodiment of the present application is first described in detail below with reference to the drawings.

[0042] like Figures 1 to 3 As shown, the composite film 100 according to the embodiment of the present application includes: a first base film 13 , a second base film 22 and a lithium replenishing layer 11 .

[0043] Specifically, the first base film 13 is disposed on one side of the lithium replenishing layer 11 and is configured to support the lithium replenishing layer 11. The second base film 22 is disposed on the side of the first base film 13 away from the lithium replenishing layer 11 and is configured to isolate the positive electrode sheet 200 and the negative electrode sheet 300.

[0044] In other words, the composite film 100 according to the embodiment of the present application is mainly composed of the first base film 13, the second base film 22 and the lithium replenishing layer 11. The composite film 100 may include the lithium replenishing layer 11, the first base film 13 and the second base film 22 arranged in sequence. When the composite film 100 is composited with the positive electrode sheet 200 and the negative electrode sheet 300, the lithium replenishing layer 11 in the composite film 100 may be attached to the negative electrode surface to achieve lithium replenishment of the negative electrode.

[0045] Specifically, the lithium replenishing layer 11 can be disposed on the surface of the first base film 13. Optionally, the lithium replenishing layer 11 can be lithium foil or lithium powder. The lithium foil or lithium powder can be coated on one side of the surface of the first base film 13. The coating method can include but is not limited to wet coating, dry rolling and 3D printing. For example, inert lithium powder can be uniformly coated on one side of the first base film 13 by wet coating to form the lithium replenishing layer 11 on the side surface.

[0046] The first base film 13 with the lithium replenishing layer 11 formed on the surface can be combined with the second base film 22 to form a composite film 100. Thus, the battery prepared by the composite film 100 includes a negative electrode sheet 300, a lithium replenishing layer 11, a first base film 13, a second base film 22 and a positive electrode sheet 200 stacked in sequence.

[0047] The first base film 13 in the composite film 100 can be used as a carrier to carry the lithium replenishing layer 11, that is, the first base film 13 mainly plays the role of carrying the lithium replenishing layer 11. Therefore, the first base film 13 can be made of any material suitable for carrying the lithium replenishing layer 11. For example, the first base film 13 can be made of non-insulating material.

[0048] The second base film 22 can be used as an insulating layer to isolate ions in the composite film 100. Therefore, the second base film 22 can be any commonly used insulating separator in the prior art to isolate the positive electrode sheet 200 and the negative electrode sheet 300.

[0049] In the process of preparing the battery, the lithium replenishing layer 11 can be formed on the surface of the first base film 13, and then the first base film 13 with the lithium replenishing layer 11 formed on the surface, the second base film 22, the positive electrode sheet 200 and the negative electrode sheet 300 are alternately stacked together to form a battery, or the first base film 13 with the lithium replenishing layer 11 formed on the surface and the second base film 22 are composited to form a composite film 100, and then the composite film 100, the positive electrode sheet 200, and the negative electrode sheet 300 are alternately stacked together to form a battery. Figure 1 The battery shown.

[0050] Thus, according to the composite film 100 of the embodiment of the present application, it includes two layers of base film and one layer of lithium replenishing layer 11. The first base film 13 is used to carry the lithium replenishing layer 11, and the lithium replenishing layer 11 can be pre-set on the composite film 100, and the second base film 22 is used to conventionally isolate the positive electrode sheet 200 and the negative electrode sheet 300. Then the composite film 100 is compounded with the positive electrode sheet 200 and the negative electrode sheet 300, which is conducive to improving the safety of the battery lithium replenishment process, avoiding the problem of severe heat generation and poor stability when the lithium metal is directly rolled with the negative electrode sheet 300. Therefore, the battery made of the composite film 100 of this embodiment can have a higher coulomb efficiency, a higher energy density and a longer cycle life. In addition, the composite film 100 of this embodiment does not need to be rolled when it is compounded with the positive electrode sheet 200 and the negative electrode sheet 300 to achieve pre-lithiation, and the pre-lithiation can be completed under a closed vacuum, solving the problem of active lithium consumption during the lithium replenishment of the negative electrode sheet 300 and the safety problem during storage.

[0051] According to one embodiment of the present application, the air permeability of the first base film 13 is less than that of the second base film 22. The air permeability refers to the oxygen permeability of 100 ml per 1 in. under a pressure of 1.22 kPa. 2 The smaller the air permeability value, the better the air permeability of the membrane. Since the air permeability value of the first base membrane 13 is smaller than that of the second base membrane 22, the pore size of the pore structure on the first base membrane 13 is larger, which is more conducive to the migration of lithium ions, and the pore size of the pore structure on the second base membrane 22 is smaller.

[0052] In the conventional technology, the lithium replenishing layer 11 is directly disposed on the base membrane. The conventional base membrane is equivalent to the second base membrane 22 in this embodiment. Since the adhesion between the lithium replenishing layer 11 and the conventional base membrane is poor, it is not conducive to composite. If the two are strongly composited, the force acting on the conventional base membrane will increase, resulting in an increase in the air permeability of the conventional base membrane, thereby affecting the ionic conductivity of the conventional base membrane.

[0053] In this embodiment, since the air permeability of the first base film 13 is smaller than that of the second base film 22, that is, the second base film 22 has a lower air permeability than the traditional base film, there are many types of first base films 13 to choose from, and after the lithium replenishing layer 11 contacts the negative electrode sheet 300, the lithium can be separated from the first base film 13, thereby ensuring the air permeability of the first base film 13 without affecting ion diffusion.

[0054] It should be noted that the air permeability of the first base film 13 and the second base film 22 may be the air permeability of the base film raw material before preparation, that is, the air permeability before compounding. In the process of preparing the composite film 100 of this embodiment, the air permeability of the first base film 13 and the second base film 22 may increase slightly after being pressed, but the air permeability of the first base film 13 can still be less than the air permeability of the second base film 22.

[0055] The air permeability value of the base film can be measured by taking the first base film 13 or the second base film 22 with a side length of 20 cm and testing it in a Wang Yan type air permeability tester.

[0056] According to a preferred embodiment of the present application, the air permeability of the first base film 13 is ≤250s / 100ml, for example, 50s / 100ml, 100s / 100ml, 150s / 100ml, 180s / 100ml, 210s / 100ml, 250s / 100ml.

[0057] Specifically, when the air permeability of the first base film 13 is greater than 250s / 100ml, the first base film 13 can still carry the lithium replenishment layer 11, thereby improving the safety of the battery's lithium replenishment process and allowing the battery to have a longer cycle life. However, the air permeability of the first base film 13 will be reduced, and the coulombic efficiency will be slightly different from that of traditional batteries.

[0058] When the air permeability of the first base film 13 is ≤250s / 100ml, the air permeability of the first base film 13 is good, which is not only beneficial to improving the safety of the battery lithium replenishment process, but also beneficial to maintaining the battery resistance at a low value, reducing the influence of the first base film 13 on lithium ion migration, and significantly improving the battery cycle life and coulomb efficiency.

[0059] In some optional embodiments of the present application, the air permeability of the second base film 22 is 100s / 100ml to 500s / 100ml.

[0060] Specifically, when the air permeability of the second base film 22 is greater than 500s / 100ml, the air permeability of the second base film 22 is poor, which affects ion diffusion and reduces the ionic conductivity of the second base film 22 .

[0061] When the air permeability of the second base film 22 is less than 100s / 100ml, the air permeability performance of the second base film 22 is too good, and the area of ​​the second base film 22 will be reduced, thereby having an adverse effect on the performance of the battery.

[0062] When the air permeability of the second base film 22 is between 100s / 100ml and 500s / 100ml, the second base film 22 has good air permeability, which can not only separate the positive electrode 200 and the negative electrode 300 to prevent short circuit between the two electrodes, but also form a channel for ion migration.

[0063] In some optional embodiments, the ionic conductivity of the first base membrane 13 is greater than the ionic conductivity of the second base membrane 22. Therefore, the first base membrane 13 is more conducive to the migration of lithium ions and improves the overall performance of the battery. At the same time, the second base membrane 22 can meet the requirements of isolating the positive electrode sheet 200 and the negative electrode sheet 300.

[0064] According to some other embodiments of the present application, the ionic conductivity of the first base film 13 is ≥6*10 -4 s / cm. For example, 6*10 -4 s / cm、7*10 -4 s / cm, 1*10 -3 s / cm、9*10 -3 s / cm, 1*10 -2 s / cm, 1*10 -1 It should be noted that the above ionic conductivity may be the ionic conductivity measured when the first base film 13 is immersed in electrolyte.

[0065] Specifically, when the ionic conductivity of the first base film 13 is less than 6*10 -4 s / cm, the first base film 13 can still play the role of supporting the lithium replenishment layer 11, thereby improving the safety of the battery lithium replenishment process. -4 s / cm, it is more conducive to the migration of lithium ions and improves the performance of the battery.

[0066] In some specific embodiments, during the production process of the composite film 100, the first base film 13 can be pressed at a pressure of 15 MPa for 600 s, and the air permeability of the first base film 13 after pressing is ≤250 s / 100 ml, and the lithium ion conductivity of the first base film 13 after soaking in the electrolyte is ≥6*10 -4 s / cm.

[0067] In some optional embodiments of the present application, the ionic conductivity of the second base film 22 is 1*10 -4 s / cm~1*10 -2 s / cm, thus, the second base film 22 can meet the requirement of isolating the positive electrode sheet 200 and the negative electrode sheet 300, and the range of materials available for the second base film 22 is wider.

[0068] In some specific embodiments of the present application, the material of the first base film 13 includes at least one of polypropylene (PP), polyethylene (PE), polyester film (PET), polyimide (PI), polyetherimide (PEI), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE).

[0069] In other words, the first base film 13 can be mainly made of one or more of the above materials. The above materials have excellent air permeability and ion conductivity, can facilitate the migration of lithium ions while carrying the lithium supplement layer 11, and improve the overall performance of the battery.

[0070] According to some optional embodiments of the present application, the thickness of the lithium replenishing layer 11 is 1 μm to 15 μm. For example, the thickness of the lithium replenishing layer 11 can be 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, or 15 μm. Setting the thickness of the lithium replenishing layer 11 to 1 μm to 15 μm can make the lithium replenishing layer 11 have sufficient thickness to compensate for the lithium source consumed in the formation of the SEI film (solid electrolyte interface film) during the first charge, thereby improving the first efficiency, energy density, and number of charge and discharge cycles of the battery.

[0071] According to some other embodiments of the present application, the surface density of the lithium supplement layer 11 is 1g / m 2 ~8g / m 2 For example, the surface density of the lithium replenishing layer 11 can be 1 g / m 2 , 2g / m 2 , 4g / m 2 , 6g / m 2 , 8g / m 2 . Set the surface density of the lithium replenishing layer 11 to be ≥1g / m 2 The negative electrode sheet 300 can be fully replenished with lithium to improve the initial efficiency, energy density and charge and discharge cycle number of the battery. The surface density of the lithium replenishment layer 11 is set to ≤8g / m 2 , the demand for lithium in the composite film 100 can be reduced while the negative electrode sheet 300 is fully replenished with lithium, thereby reducing the production cost of the composite film 100.

[0072] In some specific embodiments of the present application, an ablation layer 21 is provided on a side of the first base film 13 away from the lithium replenishing layer 11 , and the ablation layer 21 is configured to be able to chemically react with lithium.

[0073] Specifically, the position of the ablation layer 21 may include but is not limited to the following situations.

[0074] Case 1: the ablation layer 21 is disposed between the first base film 13 and the second base film 22 .

[0075] Case 2: The ablation layer 21 is disposed on a side of the second base film 22 away from the first base film 13 .

[0076] The material of the ablation layer 21 can be any material that can react chemically with lithium. Therefore, after metallic lithium pierces the first base film 13, it can react chemically with the ablation layer 21, so that the metallic lithium is blocked by the barrier formed by the ablation layer 21 and the second base film 22, thereby preventing metallic lithium from passing through the barrier formed by the ablation layer 21 and the second base film 22 to reach the positive electrode sheet 200 and cause an internal short circuit in the battery, especially avoiding safety problems caused by high-capacity lithium metal or lithium alloy negative electrodes, thereby helping to improve the safety of the battery.

[0077] In some specific embodiments, the material of the ablation layer 21 can be configured into a stable and uniform slurry, and then the slurry is coated on the surface of the second base film 22 by coating, and the coating method may include but is not limited to gravure roller coating and spraying. The second base film 22 coated with the ablation layer 21 can be combined with the first base film 13 coated with the lithium supplement layer 11, the positive electrode sheet 200 and the negative electrode sheet 300 to form a composite structure as shown in FIG. Figure 2 The battery shown.

[0078] According to some optional embodiments of the present application, the ablation layer 21 is configured to be able to undergo an intercalation reaction with lithium at 0.5V to 4V. Specifically, the intercalation reaction is a solid-phase reversible chemical reaction, and metallic lithium can be reversibly inserted into the ablation layer 21 at 0.5V to 4V. During this process, the structure of the material of the ablation layer 21 can remain unchanged, which is beneficial to improving the safety and stability of the battery.

[0079] According to some other embodiments of the present application, the electronic conductivity of the ablation layer 21 is less than 10 -7 s / cm, at this time, it is conducive to the embedding reaction between the ablation layer 21 and the metallic lithium, which effectively prevents the metallic lithium from passing through the second base film 22 to reach the positive electrode sheet 200 and causing an internal short circuit in the battery.

[0080] In some specific embodiments of the present application, the material of the ablation layer 21 includes titanium oxyfluoride (TiOF2), lithium titanate (Li4Ti5O 12 ), lithium aluminum titanium phosphate (LATP), lithium lanthanum titanate (LLTO), titanium dioxide (TiO2), tungsten oxide (WO3), zinc oxide (ZnO), and silicon dioxide (SiO).

[0081] In other words, the ablation layer 21 can be mainly made of one or more of the above materials. The above materials have low electronic conductivity and can undergo an intercalation reaction with metallic lithium at 0.5V to 4V, effectively preventing metallic lithium from passing through the second base film 22 to reach the positive electrode sheet 200 and causing an internal short circuit in the battery, thereby improving the safety of the battery.

[0082] It should be noted that when the ablation layer 21 is connected to the second base film 22 by coating, one or more of the above materials may be added with a binder to form a slurry to be coated.

[0083] According to some optional embodiments of the present application, the thickness of the ablation layer 21 is 0.5 μm to 10 μm. For example, the thickness of the ablation layer 21 may be 0.5 μm, 1 μm, 2 μm, 3 μm, 5 μm, or 10 μm.

[0084] When the thickness of the ablation layer 21 is 0.5 μm to 10 μm, the ablation layer 21 can be thick enough to prevent the ablation of metallic lithium, while preventing the ablation layer 21 from being too thick to affect the energy density of the battery.

[0085] According to some other embodiments of the present application, the surface density of the ablation layer 21 is 1 g / m 2 ~12g / m 2 For example, the surface density of the ablation layer 21 may be 1 g / m 2 , 2g / m 2 , 3g / m 2 , 5g / m 2 , 10g / m 2 , 12g / m 2 .

[0086] When the surface density of the ablation layer 21 is 1 g / m 2 ~12g / m 2 When the ablation layer 21 is formed, it can have sufficient density to block the ablation of metallic lithium and prevent the metallic lithium from passing through the ablation layer 21 and the second base layer, and it can also avoid the manufacturing cost of the ablation layer 21 being too high, which is beneficial to reducing the production cost of the composite film 100.

[0087] In some specific embodiments of the present application, a solid electrolyte layer 12 is provided between the first base film 13 and the lithium replenishing layer 11 .

[0088] Specifically, the material of the solid electrolyte layer 12 can be a material that can form a solid electrolyte. For example, the solid electrolyte layer 12 can be made of an inorganic solid electrolyte. The inorganic solid electrolyte can be configured into a stable and uniform slurry, and then the slurry is coated on the surface of the first base film 13 by coating. The coating method may include but is not limited to gravure roller coating and spraying.

[0089] The solid electrolyte layer 12 is arranged between the first base film 13 and the lithium replenishing layer 11, which can prevent the metallic lithium from clogging the pores of the first base film 13 when passing through the pores and affecting the permeability of the first base film 13. At the same time, the solid electrolyte layer 12 in the composite membrane 100 can also play the role of a solid electrolyte interface film formed during the first charging process of the battery, which is beneficial to improving the negative electrode interface.

[0090] In some specific embodiments, Figure 3As shown, the composite film 100 may include a lithium replenishing layer 11, a solid electrolyte layer 12, a first base film 13 and a second base film 22 stacked in sequence. In the preparation process of the composite film 100, the solid electrolyte may be first coated on one side of the first base film 13, and after drying, the solid electrolyte layer 12 may be formed on the surface of the first base film 13, and then metallic lithium may be coated on the side of the solid electrolyte layer 12 away from the first base film 13 to form a first diaphragm, that is, the first diaphragm includes the lithium replenishing layer 11, the solid electrolyte layer 12 and the first base film 13. Then, in the battery preparation process, the negative electrode sheet 300, the first diaphragm, the second base film 22 and the positive electrode sheet 200 are composited.

[0091] In some optional embodiments, such as Figure 4 As shown, the composite film 100 may include a lithium supplement layer 11, a solid electrolyte layer 12, a first base film 13, an ablation layer 21, and a second base film 22 stacked in sequence. In the preparation process of the composite film 100, the solid electrolyte may be first coated on one side of the first base film 13, and after drying, the solid electrolyte layer 12 may be formed on the surface of the first base film 13, and then metallic lithium may be coated on the side of the solid electrolyte layer 12 away from the first base film 13 to form a first diaphragm. The material constituting the ablation layer 21 is coated on one side of the second base film 22 to form a second diaphragm. Then, in the battery preparation process, the negative electrode sheet 300, the first diaphragm, the second diaphragm, and the positive electrode sheet 200 are composited.

[0092] In some other optional embodiments, the first separator and the second separator may be firstly combined to form a composite film 100, and then the composite film 100, the positive electrode sheet 200 and the negative electrode sheet 300 may be combined to form a battery.

[0093] According to some optional embodiments of the present application, the material of the solid electrolyte layer 12 includes at least one of lithium aluminum titanium phosphate (LATP), lithium lanthanum titanate (LLTO), lithium lanthanum zirconium oxide (LLZO), lithium phosphate (Li3PO4) and doped products thereof.

[0094] In other words, the solid electrolyte layer 12 can be mainly made of one or more of the above materials, or made of a product doped with one or more of the above materials. The above materials do not require a desolvation process, have a relatively high ion migration number, and have an ion conductivity much greater than the solid electrolyte interface film rich in Li2O and Li2CO3 components naturally formed when the battery is first charged, which is beneficial to improving the first efficiency and energy density of the battery.

[0095] It should be noted that when the solid electrolyte layer 12 is connected to the first base film 13 by coating, one or more of the above materials may be added with a binder to form a slurry to be coated.

[0096] The present application also provides a battery, which includes a positive electrode sheet 200 , a negative electrode sheet 300 and a composite film 100 . The composite film 100 is a composite film 100 according to any of the above embodiments. The lithium supplement layer 11 is located between the negative electrode sheet 300 and the first base film 13 .

[0097] Since the composite film 100 according to the embodiment of the present invention has the above-mentioned technical effects, the battery according to the embodiment of the present application also has the corresponding technical effects, that is, it is beneficial to improve the safety of the battery lithium replenishment process, avoiding the problem of severe heat generation and poor stability when lithium metal is directly rolled with the negative electrode sheet 300, so that the battery can have higher coulombic efficiency, higher energy density and longer cycle life.

[0098] In some optional embodiments, the positive electrode sheet 200 includes a positive electrode current collector and a positive electrode active material, and the positive electrode active material can be a conventional positive electrode active material in the art. For example, the positive electrode active material can include at least one of positive electrode lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, nickel cobalt aluminum ternary material (NCA) and nickel cobalt manganese ternary material (NMC), lithium manganese phosphate, lithium manganese iron phosphate, lithium iron silicate, and lithium manganese silicate.

[0099] The negative electrode sheet 300 may include a negative electrode current collector and a negative electrode active material, and the negative electrode active material may be a conventional negative electrode active material in the art, for example, the negative electrode active material may include at least one of silicon carbon, silicon oxygen, tin, graphite, and hard carbon.

[0100] The battery and the composite film 100 of the present application are described in detail below with reference to specific embodiments and comparative examples.

[0101] Comparative Example 1

[0102] S1. Fabrication of positive electrode

[0103] 960g of positive electrode active material ternary 622 (96%), 30g of binder PVDF (3%), 5g of acetylene black (0.5%), and 5g of conductive agent carbon fiber (HV) (0.5%) were added to 2000g of solvent NMP (nitrogen methyl pyrrolidone), and then stirred in a vacuum mixer to form a stable and uniform positive electrode slurry.

[0104] The positive electrode slurry was uniformly and intermittently coated on both sides of an aluminum foil (aluminum foil size: width 160 mm, thickness 16 μm) using a slit coating device; then dried at a temperature of 393 K, and pressed by a roller press to obtain a positive electrode sheet 200.

[0105] The positive electrode sheet 200 is cut into a rectangular electrode sheet with a size of 48 mm*56 mm, and the electrode ears are spot welded in the width direction.

[0106] S2. Fabrication of negative electrode

[0107] 1000 g of silicon oxide powder was added to 2000 g of water, and then 50 g of polyacrylic acid (PAA) was added and stirred vigorously to form a uniform and stable negative electrode slurry.

[0108] The negative electrode slurry was uniformly and intermittently coated on both sides of a copper foil (copper foil size: width 160 mm, thickness 8 μm) using a slit coating device; then dried at a temperature of 393 K, and pressed by a roller press to obtain a negative electrode sheet 300.

[0109] S3. Place the negative electrode sheet 300 in a drying room with a dew point of -50°C, and roll the negative electrode sheet 300 and a 6μm lithium foil (attached to a 100μm thick PET release film) to form a lithium-supplemented negative electrode. After rolling, the PET release film is peeled off from the surface of the negative electrode, and the negative electrode and the lithium-supplementing layer 11 are rolled up together.

[0110] S4. Battery production

[0111] The positive electrode sheet 200 obtained in step S1, the lithium-supplemented negative electrode obtained in step S3, the first base film 13 and the first base film 13 are alternately stacked together to prepare a battery by lamination, wherein the positive electrode sheet 200 and the lithium-supplemented negative electrode are alternately separated by a separator composed of the first base film 13 and the second base film 22, to obtain a dry battery cell. The material of the first base film 13 is PET non-woven fabric, and the size of the separator is: width 1200mm, thickness 6μm, and the material of the second base film 22 is PP film, and the size of the separator is: width 1200mm, thickness 8μm.

[0112] The prepared dry battery cell is placed in an aluminum-plastic film outer package, and the electrolyte is injected, and then vacuum-sealed, and then placed at 60°C for 48 hours, pressurized at 45°C, repackaged, vented, and divided to obtain a lithium battery. Among them, the air permeability of the first base film 13 is 240s / 100ml, and the ionic conductivity is 9.9*10 -3 The air permeability of the second base film 22 is 260s / 100ml, and the ionic conductivity is 1.09*10 -3 S / cm.

[0113] Comparative Example 2

[0114] The same step S1 as in Comparative Example 1 is used to obtain the positive electrode sheet 200 and the same step S2 is used to obtain the negative electrode sheet 300 .

[0115] The inert lithium powder is evenly sprayed on the surface of the first base film 13 by electrostatic powder spraying equipment, and the first base film 13 containing the lithium replenishing layer 11 is obtained after rolling, wherein the lithium replenishing layer 11 has a thickness of 6 μm. The first base film 13 is made of PE material and has a thickness of 12 μm.

[0116] The positive electrode sheets 200, the first base film 13 containing the lithium supplement layer 11, and the negative electrode sheets 300 are alternately stacked together to prepare a battery by lamination, wherein the positive electrode sheets 200 and the negative electrode sheets 300 are alternately isolated by the first base film 13 to obtain a dry battery cell.

[0117] The prepared dry battery cell is placed in an aluminum-plastic film outer package, and the electrolyte is injected, and then vacuum-sealed, and then placed at 60°C for 48 hours, pressurized at 45°C, repackaged, vented, and divided to obtain a lithium battery. Among them, the air permeability of the first base film 13 is 240s / 100ml, and the ionic conductivity is 9.9*10 -3 S / cm.

[0118] Comparative Example 3

[0119] The same step S1 as in Comparative Example 1 is used to obtain the positive electrode sheet 200 and the same step S2 is used to obtain the negative electrode sheet 300 .

[0120] The inert lithium powder is evenly sprayed on the surface of the second base film 22 by electrostatic powder spraying equipment, and the second base film 22 containing the lithium replenishing layer 11 is obtained after rolling, wherein the lithium replenishing layer 11 has a thickness of 6 μm. The second base film 22 is made of PP material and has a thickness of 12 μm.

[0121] The positive electrode sheets 200, the second base film 22 containing the lithium supplement layer 11, and the negative electrode sheets 300 are alternately stacked together to prepare a battery by lamination, wherein the positive electrode sheets 200 and the negative electrode sheets 300 are alternately isolated by the second base film 22 to obtain a dry battery cell.

[0122] The prepared dry battery cell is placed in an aluminum-plastic film outer package, and the electrolyte is injected, and then vacuum-sealed, and then placed at 60°C for 48 hours, pressurized at 45°C, secondary packaged, exhausted, and capacity divided to obtain a lithium battery. The second base film 22 has an air permeability of 260s / 100ml and an ionic conductivity of 1.58*10 -3 S / cm.

[0123] Example 1

[0124] The same step S1 as in Comparative Example 1 is used to obtain the positive electrode sheet 200 and the same step S2 is used to obtain the negative electrode sheet 300 .

[0125] The first base film 13 is placed in a drying room, and an electrostatic powder spraying device is used to evenly spray inert lithium powder on the surface of the first base film 13, and after rolling, the first base film 13 containing the lithium replenishing layer 11 is obtained, wherein the lithium replenishing layer 11 has a thickness of 4 μm. The first base film 13 is made of PE material and has a thickness of 6 μm.

[0126] The positive electrode sheet 200, the first base film 13 containing the lithium supplement layer 11, the second base film 22 and the negative electrode sheet 300 are alternately stacked together to prepare a battery by stacking, wherein the first base film 13 containing the lithium supplement layer 11 and the second base film 22 are formed as follows: Figure 1 The composite film 100 shown, the positive electrode sheet 200 and the negative electrode sheet 300 are alternately isolated by the composite film 100 to obtain a dry battery cell. The second base film 22 has a thickness of 4 μm and is made of PP. During the battery preparation process, the lithium supplement layer 11 on the surface of the first base film 13 is close to the negative electrode sheet 300.

[0127] The prepared dry battery cell is placed in an aluminum-plastic film outer package, injected with electrolyte, and then vacuum-sealed, placed at 60°C for 48 hours, pressurized at 45°C, repackaged, exhausted, and divided into different capacities to obtain a lithium battery.

[0128] The air permeability of the first base film 13 is 240s / 100ml, and the ionic conductivity is 9.9*10 -3 The air permeability of the second base film 22 is 260s / 100ml, and the ionic conductivity is 9.9*10 -4 S / cm.

[0129] Example 2

[0130] The same step S1 as in Comparative Example 1 is used to obtain the positive electrode sheet 200 and the same step S2 is used to obtain the negative electrode sheet 300 .

[0131] The first base film 13 is placed in a drying room, and an electrostatic powder spraying device is used to evenly spray inert lithium powder on the surface of the first base film 13, and after rolling, the first base film 13 containing the lithium replenishing layer 11 is obtained, wherein the lithium replenishing layer 11 has a thickness of 4 μm. The first base film 13 is made of PE material and has a thickness of 9 μm.

[0132] 5000g of titanium oxyfluoride powder was added to 20000g of water, and then 500g of polyacrylic acid (PAA) was added and vigorously stirred to form a uniform and stable titanium oxyfluoride slurry; the titanium oxyfluoride slurry was evenly coated on a single surface of the second base film 22 using a gravure roller coating device, wherein the coating thickness was 3μm; and then dried at a temperature of 383K to obtain the second base film 22 coated with the ablation layer 21. The second base film 22 was made of PP and had a thickness of 4μm.

[0133] The positive electrode sheet 200, the first base film 13 containing the lithium supplement layer 11, the second base film 22 coated with the ablation layer 21 and the negative electrode sheet 300 are alternately stacked together to prepare a battery by stacking, wherein the first base film 13 containing the lithium supplement layer 11 and the second base film 22 coated with the ablation layer 21 form a Figure 3The composite film 100 shown, the positive electrode sheet 200 and the negative electrode sheet 300 are alternately isolated by the composite film 100 to obtain a dry battery cell. During the battery preparation process, the lithium replenishing layer 11 on the surface of the first base film 13 is close to the negative electrode sheet 300, and the ablation layer 21 on the surface of the second base film 22 is close to the first base film 13.

[0134] The prepared dry battery cell is placed in an aluminum-plastic film outer package, and the electrolyte is injected, and then vacuum-sealed, and then placed at 60°C for 48 hours, pressurized at 45°C, repackaged, vented, and divided to obtain a lithium battery. Among them, the air permeability of the first base film 13 is 220s / 100ml, and the ionic conductivity is 9.1*10 -3 The air permeability of the second base film 22 is 260s / 100ml, and the ionic conductivity is 9.9*10 -4 S / cm.

[0135] Example 3

[0136] The same step S1 as in Comparative Example 1 is used to obtain the positive electrode sheet 200 and the same step S2 is used to obtain the negative electrode sheet 300 .

[0137] The first base film 13 is placed in a drying room, and an electrostatic powder spraying device is used to evenly spray inert lithium powder on the surface of the first base film 13, and after rolling, the first base film 13 containing the lithium replenishing layer 11 is obtained, wherein the lithium replenishing layer 11 has a thickness of 4 μm. The first base film 13 is made of PI non-woven fabric and has a thickness of 8 μm.

[0138] 5000g of titanium oxyfluoride powder was added to 20000g of water, and then 500g of polyacrylic acid (PAA) was added and vigorously stirred to form a uniform and stable titanium oxyfluoride slurry; the titanium oxyfluoride slurry was evenly coated on a single surface of the second base film 22 using a gravure roller coating device, wherein the coating thickness was 2μm; and then dried at a temperature of 383K to obtain the second base film 22 coated with the ablation layer 21. The second base film 22 was made of PP and had a thickness of 4μm.

[0139] The positive electrode sheet 200, the first base film 13 containing the lithium supplement layer 11, the second base film 22 coated with the ablation layer 21 and the negative electrode sheet 300 are alternately stacked together to prepare a battery by lamination, wherein the first base film 13 containing the lithium supplement layer 11 and the second base film 22 coated with the ablation layer 21 form a composite film 100, and the positive electrode sheet 200 and the negative electrode sheet 300 are alternately isolated by the composite film 100 to obtain a dry battery cell. During the battery preparation process, the lithium supplement layer 11 on the surface of the first base film 13 is close to the negative electrode sheet 300, and the ablation layer 21 on the surface of the second base film 22 is close to the positive electrode sheet 200.

[0140] The prepared dry battery cell is placed in an aluminum-plastic film outer package, and the electrolyte is injected, and then vacuum-sealed, and then placed at 60°C for 48 hours, pressurized at 45°C, repackaged, vented, and divided to obtain a lithium battery. The air permeability of the first base film 13 is 180s / 100ml, and the ionic conductivity is 10.6*10 -3 The air permeability of the second base film 22 is 260s / 100ml, and the ionic conductivity is 9.9*10 -4 S / cm.

[0141] Example 4

[0142] The same step S1 as in Comparative Example 1 is used to obtain the positive electrode sheet 200 and the same step S2 is used to obtain the negative electrode sheet 300 .

[0143] The first base film 13 is placed in a drying room, and an electrostatic powder spraying device is used to evenly spray inert lithium powder on the surface of the first base film 13, and after rolling, the first base film 13 containing the lithium replenishing layer 11 is obtained, wherein the lithium replenishing layer 11 has a thickness of 4 μm. The first base film 13 is made of PEI (polyetherimide) and has a thickness of 10 μm.

[0144] 5000g of titanium oxyfluoride powder was added to 20000g of water, and then 500g of polyacrylic acid (PAA) was added and vigorously stirred to form a uniform and stable titanium oxyfluoride slurry; the titanium oxyfluoride slurry was evenly coated on a single surface of the second base film 22 using a gravure roller coating device, wherein the coating thickness was 2μm; and then dried at a temperature of 383K to obtain the second base film 22 coated with the ablation layer 21. The second base film 22 was made of PP and had a thickness of 4μm.

[0145] The positive electrode sheet 200, the first base film 13 containing the lithium supplement layer 11, the second base film 22 coated with the ablation layer 21 and the negative electrode sheet 300 are alternately stacked together to prepare a battery by lamination, wherein the first base film 13 containing the lithium supplement layer 11 and the second base film 22 coated with the ablation layer 21 form a composite film 100, and the positive electrode sheet 200 and the negative electrode sheet 300 are alternately isolated by the composite film 100 to obtain a dry battery cell. During the battery preparation process, the lithium supplement layer 11 on the surface of the first base film 13 is close to the negative electrode sheet 300, and the ablation layer 21 on the surface of the second base film 22 is close to the first base film 13.

[0146] The prepared dry battery cell is placed in an aluminum-plastic film outer package, and the electrolyte is injected, and then vacuum-sealed, and then placed at 60°C for 48 hours, pressurized at 45°C, repackaged, vented, and divided to obtain a lithium battery. The air permeability of the first base film 13 is 150s / 100ml, and the ionic conductivity is 9.4*10 -2 The air permeability of the second base film 22 is 260s / 100ml, and the ionic conductivity is 9.9*10 -4 S / cm.

[0147] Example 5

[0148] The same step S1 as in Comparative Example 1 is used to obtain the positive electrode sheet 200 and the same step S2 is used to obtain the negative electrode sheet 300 .

[0149] 5000g of lithium aluminum titanium phosphate powder was added to 15000g of water, and then 200g of polyacrylic acid (PAA) was added, and stirred vigorously to form a uniform and stable solid electrolyte slurry. The solid electrolyte slurry was evenly coated on a single surface of the first base film 13 using a gravure roller coating device. The first base film 13 was made of PET, with a thickness of 6μm and a coating layer thickness of 2μm; and then dried at 383K to obtain the first base film 13 coated with a solid electrolyte.

[0150] The first base film 13 coated with solid electrolyte is placed in a drying room, and inert lithium powder is evenly sprayed on the surface of the first base film 13 using an electrostatic powder spraying device. After rolling, the first base film 13 containing the lithium replenishing layer 11 is obtained, wherein the thickness of the lithium replenishing layer 11 is 6 μm.

[0151] The positive electrode sheet 200, the first base film 13 containing the lithium supplement layer 11 and the solid electrolyte, the second base film 22 and the negative electrode sheet 300 are alternately stacked together to prepare a battery by stacking, wherein the first base film 13 containing the lithium supplement layer 11 and the solid electrolyte layer 12 and the second base film 22 are formed as follows: Figure 2 The composite film 100 shown, the positive electrode sheet 200 and the negative electrode sheet 300 are alternately isolated by the composite film 100 to obtain a dry battery cell. The first base film 13 has a thickness of 4 μm and is made of PP. During the battery preparation process, the lithium supplement layer 11 on the surface of the first base film 13 is close to the negative electrode sheet 300.

[0152] The prepared dry battery cell is placed in an aluminum-plastic film outer package, and the electrolyte is injected, and then vacuum-sealed, and then placed at 60°C for 48 hours, pressurized at 45°C, repackaged, vented, and divided into different volumes to obtain a lithium battery. The air permeability of the first base film 13 is 130s / 100ml, and the ionic conductivity is 10.2*10 -3 The air permeability of the second base film 22 is 260s / 100ml, and the ionic conductivity is 9.9*10 -4 S / cm.

[0153] Example 6

[0154] The same step S1 as in Comparative Example 1 is used to obtain the positive electrode sheet 200 and the same step S2 is used to obtain the negative electrode sheet 300 .

[0155] like Figure 7As shown, 5000g of lithium aluminum titanium phosphate powder is added to 15000g of water, and then 200g of polyacrylic acid (PAA) is added, and vigorously stirred to form a uniform and stable solid electrolyte slurry. The solid electrolyte slurry is evenly coated on a single surface of the first base film 13 using a gravure roller coating device. The first base film 13 is made of PET material, has a thickness of 6μm, and a coating layer thickness of 2μm; then dried at 383K to obtain the first base film 13 coated with a solid electrolyte, which is SP1.

[0156] The first base film 13 coated with the solid electrolyte is placed in a drying room, and the inert lithium powder is evenly sprayed on the surface of the first base film 13 coated with the solid electrolyte using an electrostatic powder spraying device. After rolling, the first base film 13 containing the lithium replenishing layer 11 is obtained. The first base film 13 is SP2, and the thickness of the lithium replenishing layer 11 is 6 μm.

[0157] 5000g of titanium oxyfluoride powder was added to 20000g of water, and then 500g of polyacrylic acid (PAA) was added and vigorously stirred to form a uniform and stable titanium oxyfluoride slurry; the titanium oxyfluoride slurry was evenly coated on a single surface of the second base film 22 using a gravure roller coating device, wherein the coating thickness was 3μm; and then dried at a temperature of 383K to obtain a second base film 22 coated with an ablation layer 21, the second base film 22 being TP1. The second base film 22 was made of PP and had a thickness of 8μm.

[0158] The positive electrode sheet 200, the first base film 13 containing the lithium supplement layer 11 and the solid electrolyte layer 12, the second base film 22 coated with the ablation layer 21 and the negative electrode sheet 300 are alternately stacked together to prepare a battery by stacking, wherein the lithium supplement layer 11, the solid electrolyte layer 12, the first base film 13, the ablation layer 21 and the second base film 22 are formed as follows Figure 4 The composite film 100 shown, the positive electrode sheet 200 and the negative electrode sheet 300 are alternately isolated by the composite film 100 to obtain a dry battery cell. The first base film 13 has a thickness of 4 μm and is made of PP. During the battery preparation process, the lithium supplement layer 11 on the surface of the first base film 13 is close to the negative electrode sheet 300.

[0159] The prepared dry battery cell is placed in an aluminum-plastic film outer package, and the electrolyte is injected, and then vacuum-sealed, and then placed at 60°C for 48 hours, pressurized at 45°C, repackaged, vented, and divided to obtain a lithium battery. The air permeability of the first base film 13 is 100s / 100ml, and the ionic conductivity is 10.2*10 -2 The air permeability of the second base film 22 is 260s / 100ml, and the ionic conductivity is 9.9*10 -4 S / cm.

[0160] Example 7

[0161] The same step S1 as in Comparative Example 1 is used to obtain the positive electrode sheet 200 and the same step S2 is used to obtain the negative electrode sheet 300 .

[0162] The first base film 13 is placed in a drying room, and an electrostatic powder spraying device is used to evenly spray inert lithium powder on the surface of the first base film 13. After rolling, the first base film 13 containing the lithium supplement layer 11 is obtained, wherein the lithium supplement layer 11 has a thickness of 4 μm. The first base film 13 is made of PE material, has a thickness of 12 μm, and is a high-porosity diaphragm.

[0163] The positive electrode sheet 200, the first base film 13 containing the lithium supplement layer 11, the second base film 22 and the negative electrode sheet 300 are alternately stacked together to prepare a battery by stacking, wherein the first base film 13 containing the lithium supplement layer 11 and the second base film 22 are formed as follows: Figure 1 The composite film 100 shown, the positive electrode sheet 200 and the negative electrode sheet 300 are alternately separated by the composite film 100 to obtain a dry battery cell. The first base film 13 has a thickness of 12 μm and is made of PE, which is a low-porosity separator. During the battery preparation process, the lithium supplement layer 11 on the surface of the first base film 13 is close to the negative electrode sheet 300.

[0164] The prepared dry battery cell is placed in an aluminum-plastic film outer package, and the electrolyte is injected, and then vacuum-sealed, and then placed at 60°C for 48 hours, pressurized at 45°C, repackaged, vented, and divided to obtain a lithium battery. The air permeability of the first base film 13 is 280s / 100ml, and the ionic conductivity is 8.8*10 -3 The air permeability of the second base film 22 is 260s / 100ml, and the ionic conductivity is 9.9*10 -4 S / cm.

[0165] Example 8

[0166] The same step S1 as in Comparative Example 1 is used to obtain the positive electrode sheet 200 and the same step S2 is used to obtain the negative electrode sheet 300 .

[0167] The first base film 13 is placed in a drying room, and an electrostatic powder spraying device is used to evenly spray inert lithium powder on the surface of the first base film 13, and after rolling, the first base film 13 containing the lithium replenishing layer 11 is obtained, wherein the lithium replenishing layer 11 has a thickness of 4 μm. The first base film 13 is made of PE material and has a thickness of 12 μm.

[0168] The positive electrode sheet 200, the first base film 13 containing the lithium supplement layer 11, the second base film 22 and the negative electrode sheet 300 are alternately stacked together to prepare a battery by stacking, wherein the first base film 13 containing the lithium supplement layer 11 and the second base film 22 are formed as follows: Figure 1The composite film 100 shown, the positive electrode sheet 200 and the negative electrode sheet 300 are alternately isolated by the composite film 100 to obtain a dry battery cell. The first base film 13 has a thickness of 12 μm and is made of PE. During the battery preparation process, the lithium supplement layer 11 on the surface of the first base film 13 is close to the negative electrode sheet 300.

[0169] The prepared dry battery cell is placed in an aluminum-plastic film outer package, and the electrolyte is injected, and then vacuum-sealed, and then placed at 60°C for 48 hours, pressurized at 45°C, repackaged, vented, and divided to obtain a lithium battery. The air permeability of the first base film 13 is 250s / 100ml, and the ionic conductivity is 7.0*10 -4 The air permeability of the second base film 22 is 250s / 100ml, and the ionic conductivity is 5.5*10 -4 S / cm.

[0170] For the sake of comparison, the material composition and structure of the composite membrane 100 in the battery of Comparative Examples 1 to 3 and Examples 1 to 8 are listed in Table 1. The air permeability and ionic conductivity of the first base membrane 13 and the second base membrane 22 for preparing each composite membrane 100 are listed in Table 2.

[0171] Table 1 Material composition and structure of composite membrane

[0172]

[0173] Table 2 Properties of the first base film 13 and the second base film 22 used to prepare the composite film 100

[0174]

[0175] The batteries of Comparative Examples 1 to 3 and Examples 1 to 8 were tested below.

[0176] Take 5 batteries prepared in each comparative example and embodiment, and test the coulombic efficiency and charge-discharge cycle of the battery at 0.2C on a LAND CT 2001C secondary battery performance tester at 25±1°C. The steps are as follows:

[0177] Set aside for 10 minutes;

[0178] Constant voltage charging to 4.2V / 0.05C cut off;

[0179] Set aside for 10 minutes;

[0180] Discharging at constant current until 3.0V is considered one cycle.

[0181] The ratio of the first discharge capacity to the first charge capacity is the first coulomb efficiency. Repeat the above steps. When the battery capacity is less than 80% of the first discharge capacity during the cycle, the cycle is terminated. The number of cycles is the cycle life of the battery, and the average value is taken for each group. After the cycle life is over, the size of the battery is tested and the battery expansion rate is calculated by comparing it with the size before the cycle. The test results are shown in Table 3 below.

[0182] Table 3 Performance comparison

[0183] Label Cycle times Capacity retention rate Coulomb efficiency Comparative Example 1 252 80% 99.93% Comparative Example 2 736 80% 99.95% Comparative Example 3 426 80% 99.91% Example 1 1765 80% 99.96% Example 2 2033 80% 99.98% Example 3 2176 80% 99.98% Example 4 1987 80% 99.97% Example 5 1839 80% 99.97% Example 6 2250 80% 99.98% Example 7 1400 80% 99.95% Example 8 1670 80% 99.96%

[0184] As can be seen from Table 2, in Comparative Example 1, the metal lithium and the negative electrode sheet 300 are roll-formed by rolling in the conventional technology. Although the first base film 13 and the second base film 22 are provided between the positive electrode sheet 200 and the negative electrode sheet 300, the corresponding cycle number and coulomb efficiency of the battery are both at a low level. In Comparative Examples 2 and 3, the metal lithium is coated on the first base film 13 and the second base film 22, respectively, and there is only one base film between each group of positive electrode sheets 200 and negative electrode sheets 300. At this time, the corresponding cycle number and coulomb efficiency of the battery are still at a low level.

[0185] In Example 1, metallic lithium is coated on the first base film 13, and two layers of base films are arranged between the positive electrode sheet 200 and the negative electrode sheet 300. The first base film 13 is used to carry metallic lithium, and then the two layers of base films are compounded with the positive electrode sheet 200 and the negative electrode sheet 300. The corresponding number of cycles of the battery is 1765 times, which is limited compared with Comparative Examples 1 to 2. At the same time, the coulombic efficiency of the battery in the embodiment is 99.96%, which is also better than any of the comparative examples. Therefore, the composite film 100 composed of the lithium supplement layer 11 and the two layers of base films in the embodiment of the present application can significantly improve the coulombic efficiency and cycle life of the battery.

[0186] In Examples 2 to 4, the composite film 100 is composed of a lithium replenishing layer 11, a first base film 13, an ablation layer 21 and a second base film 22, wherein the ablation layer 21 in Example 2 is located between the first base film 13 and the second base film 22, and the ablation layer 21 in Examples 3 to 4 is located on the side of the second base film 22 away from the first base film 13. It can be seen from Table 2 that after the ablation layer 21 is added to the composite film 100, the cycle number and coulomb efficiency of the battery are greater than the cycle number and coulomb efficiency of the battery in Example 1, therefore, adding the ablation layer 21 to the composite film 100 is conducive to further improving the coulomb efficiency and cycle life of the battery.

[0187] In Example 5, the composite film 100 is composed of a lithium supplement layer 11, a solid electrolyte layer 12, a first base film 13 and a second base film 22. As can be seen from Table 2, after adding the solid electrolyte layer 12 to the composite film 100, the number of cycles of the battery increases from 1765 times in Example 1 to 1839 times, and the coulombic efficiency also increases from 99.96% to 99.97%. Therefore, adding the solid electrolyte layer 12 to the composite film 100 is conducive to further improving the coulombic efficiency and cycle life of the battery.

[0188] In Example 6, the composite film 100 is composed of a lithium supplement layer 11, a solid electrolyte layer 12, a first base film 13, an ablation layer 21, and a second base film 22. As can be seen from Table 2, the battery of Example 6 has the largest number of cycles of 2250 times and the largest coulombic efficiency of 99.98% among all the embodiments. Therefore, adding a solid electrolyte layer 12 and an ablation layer 21 to the composite film 100 can further improve the coulombic efficiency and cycle life of the battery.

[0189] In Example 7, the air permeability of the first base film 13 is 280s / 100ml, which is higher than 250s / 100ml, and the air permeability of the first base film 13 is greater than the air permeability of the second base film 22. The corresponding battery cycle number is 1400, and the coulombic efficiency is 99.95%. Comparing Example 7 with the three comparative examples, the number of cycles of Example 7 is significantly better than the three comparative examples. Although the coulombic efficiency is not improved compared with Comparative Example 2, it can be seen that the composite film 100 of Example 7 is still beneficial to improving the cycle life of the battery. Comparing Example 7 with Examples 1 to 6, it can be seen that the use of a first base film 13 with an air permeability of less than 250s / 100ml is beneficial to improving the coulombic efficiency of the battery.

[0190] In Example 8, two base films of the same material and the same thickness are used, so that the air permeability value of the first base film 13 is equal to that of the second base film 22, both of which are 250s / 100ml. The corresponding battery cycle number is 1670, which is significantly improved compared with the three comparative examples, and its coulombic efficiency is 99.96%. Although it is greater than any comparative example, the improvement is small. Compared with Implementation 2 to Implementation 6, it can be seen that when the air permeability value of the first base film 13 is greater than the permeability value of the second base film 22, the coulombic efficiency of the battery can be more significantly improved.

[0191] It should be noted that, according to experiments, the material and thickness of the first base film 13 and the second base film 22 have little effect on the coulombic efficiency and cycle life of the battery.

[0192] In summary, the composite membrane 100 according to the embodiment of the present invention includes at least two base membranes and a lithium replenishing layer 11. The lithium replenishing layer 11 is carried by the first base membrane 13, and the lithium replenishing layer 11 can be pre-set on the composite membrane 100, and then the composite membrane 100 is composited with the positive electrode sheet 200 and the negative electrode sheet 300, which is beneficial to improve the safety of the battery lithium replenishment process and avoid the problem of severe heat generation and poor stability when lithium metal is directly rolled with the negative electrode sheet 300. Therefore, the battery made of the composite membrane 100 of this embodiment can have higher coulombic efficiency, higher energy density and longer cycle life.

[0193] Although some specific embodiments of the present application have been described in detail by way of example, it should be understood by those skilled in the art that the above examples are only for illustration, not for limiting the scope of the present application. It should be understood by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present application. The scope of the present application is defined by the appended claims.

Claims

1. A composite film, characterized in that include: Lithium replenishment layer; A first base film, the first base film is disposed on one side of the lithium replenishing layer, and the first base film is configured to be suitable for supporting the lithium replenishing layer; A second base film, wherein the second base film is disposed on a side of the first base film away from the lithium replenishing layer, and the second base film is configured to isolate the positive electrode sheet and the negative electrode sheet.

2. The composite membrane according to claim 1, characterized in that The air permeability value of the first base film is lower than the air permeability value of the second base film.

3. The composite membrane according to claim 1, characterized in that The air permeability of the first base film is ≤250s / 100ml.

4. The composite membrane according to claim 1, characterized in that The air permeability of the second base film is 100s / 100ml to 500s / 100ml.

5. The composite membrane according to claim 1, characterized in that The ionic conductivity of the first base film is greater than the ionic conductivity of the second base film.

6. The composite membrane according to claim 1, characterized in that The ionic conductivity of the first base film is ≥6*10 -4 s / cm.

7. The composite membrane according to claim 1, characterized in that The ionic conductivity of the second base film is 1*10 -4 s / cm~1*10 -2 s / cm.

8. The composite membrane according to claim 1, characterized in that The material of the first base film includes at least one of polypropylene, polyethylene, polyester film, polyimide, polyetherimide, polyvinyl alcohol, polyacrylic acid, polyvinylidene fluoride, and polytetrafluoroethylene.

9. The composite membrane according to claim 1, characterized in that The lithium replenishment layer satisfies at least one of the following conditions: The thickness of the lithium supplement layer is 1 μm to 15 μm; The surface density of the lithium supplement layer is 1 g / m 2 ~8g / m 2 .

10. The composite membrane according to claim 1, characterized in that An ablation layer is provided on a side of the first base film away from the lithium supplement layer, and the ablation layer is configured to be able to chemically react with lithium.

11. The composite membrane according to claim 10, characterized in that The ablation layer satisfies at least one of the following conditions: The ablation layer is configured to be capable of undergoing an intercalation reaction with lithium at 0.5V to 4V; The electronic conductivity of the ablation layer is less than 10 -7 s / cm; The thickness of the ablation layer is 0.5 μm to 10 μm; The surface density of the ablation layer is 1 g / m 2 ~12g / m 2 .

12. The composite membrane according to claim 10, characterized in that The material of the ablation layer includes at least one of titanium oxyfluoride, lithium titanate, lithium aluminum titanium phosphate, lithium lanthanum titanate, titanium dioxide, tungsten oxide, zinc oxide, and silicon oxide.

13. The composite membrane according to any one of claims 1 to 12, characterized in that A solid electrolyte layer is provided between the first base film and the lithium replenishing layer.

14. The composite membrane according to claim 13, characterized in that The material of the solid electrolyte layer includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum zirconium oxide, lithium phosphate and doped products thereof.

15. A battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and a composite film, wherein the composite film is the composite film according to any one of claims 1 to 14, and the lithium replenishing layer is located between the negative electrode sheet and the first base film.

16. An electrical equipment, characterized in that: Comprising the battery as claimed in claim 15.

Citation Information

Patent Citations

  • Double-layer composite diaphragm cell and lithium supplement method thereof

    CN107845829A

  • Lithium supplementing diaphragm, preparation method thereof and lithium ion battery

    CN112531284A

  • Composite diaphragm with lithium supplementing effect, and preparation method thereof and lithium ion battery

    CN112599928A

  • Diaphragm and battery

    CN115332725A

  • Lithium-ion battery and manufacturing method for lithium-ion battery

    JP2020030924A